Mycoplasma pneumonia with persistent lymphadenopathy and severe cold agglutinin haemolysis. (2016) - Shah, Mit; Khan, Sajid; Chan, Kenneth
Abstract: Mycoplasma pneumonia is an atypical pneumonia commonly affecting young patients with generally mild clinical course. We present a case of a 66-year-old female presenting with weight loss, night sweats and low-grade pyrexia. She acquired symptomatic haemolytic anaemia requiring blood transfusion, markedly raised erythrocyte sedimentation rate (ESR) to 114 mm/hr and extensive peri-hilar lymphadenopathy on computed tomography (CT) scan. After excluding malignancy and granulomatous diseases, she made good recovery although a 4 week follow-up CT scan showed persistent but resolving lymphadenopathy. We discuss the considerations for blood transfusion in cold agglutinin disease, and the investigations for immunological manifestations in Mycoplasma pneumonia.